Epipelic diatom assemblages to determine water quality in the Tuntang River downstream, Demak, Central Java. Issue 1 (1st January 2023) - Al Falah, M H; Soeprobowati, T R; Hadiyanto,
Abstract: Tuntang River downstream, located in the Demak Regency, Central Java, frequently experiences floods caused by sedimentation, which has occurred continuously since 1970. Changes in land use resulted in ample surface runoff water. The phenomenon affects society's activities around the Tuntang River downstream which can hinder their activities. The study aimed to analyze diatoms with a biological index and investigate their effect on water quality. Diatoms are one of the bioindicators describing water quality in the river. The sampling technique was used through purposive sampling by selecting four stations along the Tuntang River downstream. The extraction method of sediment was carried out with HCl and H2 O2 as the solution. The results showed 59 species with 38363 individuals/gram from all research stations. The results showed the highest diversity index (H') at station 4 (2.96), the highest uniformity index (e) at station 3 (0.68), and the highest dominance index (D) at station 1 (0.11), respectively. Nitzschia palea indicates the waters containing high C organic and meso-eutrophic based on the dominant species. The results' findings are expected to become references for river management in the Tuntang River downstream.